2022
DOI: 10.1108/jica-02-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Crisis and mental health of working women: risk factors and integrated care interventions based on organizational, individual, and institutional partnership

Abstract: PurposeCrises can weigh heavily on individuals' mental health. COVID-19 is a crisis that has shaken humanity, plunging it into a great wave of fear, ambiguity and uncertainty, due to its novelty and rapid spread, as well as lethality. Mental health disparities between women and men have widened as a result of this pandemic. Stress factors have multiplied, especially among working women, making them more psychologically vulnerable than they were before this pandemic and easy prey to psychological distress. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…During the pandemic, teleworking created blurred work-private life boundaries for individuals (Hamouche, 2021b), with the possibility of multiple family interruptions (Prajogo et al, 2020). Furthermore, it generated social isolation, which had negative impacts on employees' mental health (Hamouche, 2021b(Hamouche, , 2022Straus et al, 2022). In this context, the study by Golden et al (2008) on teleworkers revealed that professional isolation generated by teleworking negatively impacts job performance, which can be intensified based on the amount of time spent teleworking.…”
Section: Integrative Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…During the pandemic, teleworking created blurred work-private life boundaries for individuals (Hamouche, 2021b), with the possibility of multiple family interruptions (Prajogo et al, 2020). Furthermore, it generated social isolation, which had negative impacts on employees' mental health (Hamouche, 2021b(Hamouche, , 2022Straus et al, 2022). In this context, the study by Golden et al (2008) on teleworkers revealed that professional isolation generated by teleworking negatively impacts job performance, which can be intensified based on the amount of time spent teleworking.…”
Section: Integrative Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Job performance is essential to sustain organizations and ensure their success (Bruggen, 2015), however, it can be significantly challenged in times of crisis, such as the COVID-19 pandemic that has shaken organizations worldwide, generating a financial shock, instability and uncertainty. Organizations needed to ensure the implementation of non-pharmaceutical measures (physical distancing, lockdown and quarantines) to prevent the spread of the virus among their employees, but also to find effective ways to sustain their business and maintain employees' performance (Liu et al, 2021;Hamouche, 2021aHamouche, , 2022. In this context, teleworking is a work arrangement that has been widely adopted (Lee, 2021), to ensure the continuity of organizational operations and maintain employees' performance, mainly in the case of industries and job positions that can be performed remotely, from home.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of the COVID-19 crisis, reports indicate that the prevalence of fear, loneliness, boredom, loss of control, as well as feelings of insecurity, is very high (Xiao, 2020). Thus, COVID-19 has triggered feelings of fear in most people (Hamouche, 2023;Yıldırım and G€ uler, 2022), which made them adopt preventive behaviors. One of these behaviors may be avoiding engaging in volunteer activities.…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…Indeed, studies revealed that COVID-19 generated a “great resignation” sweeping worldwide workplaces (Allman, 2021; Sheather and Slattery, 2021). Many individuals were either quitting their job or looking for a career change (Allman, 2021), and this can weigh heavily on sectors already suffering from a workforce shortage, such as healthcare (Hamouche and Chabani, 2021; Sheather and Slattery, 2021; Hamouche, 2022). In the US, for example, the Bureau of Labor Statistics (2021) showed that the quitting level and rate increased to a series high of 4 million and 2.7%, in April 2021.…”
Section: Introductionmentioning
confidence: 99%